2010
DOI: 10.4269/ajtmh.2010.09-0040
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effect of Local and Global Spatial Variation on a Mosquito-Borne Infection in a Neotropical Heterogeneous Environment

Abstract: Mosquito-borne pathogen transmission exhibits spatial-temporal variability caused by ecological interactions acting at different scales. We used local spatial statistics and geographically weighted regression (GWR) to determine the spatial pattern of malaria incidence and persistence in northeastern Venezuela. Seven to 11 hot spots of malaria transmission were detected by using local spatial statistics, although disease persistence was explained only for four of those hot spots. The GWR models greatly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Understanding the importance of these factors is particularly critical for endemic Hawaiian species that continue to undergo steep population declines and range restrictions as climate warms. Like human malaria, spatial patterns of avian malaria are driven by exogenous temperatures, altitude, rainfall, and suitable habitat for larval mosquitoes to complete their life cycle (Balls et al 2004, Pascual et al 2008, Grillet et al 2010, Grillet et al 2014. As a result avian malaria in Hawaii may provide a seminal model to understand the environmental and ecological drivers of human malaria and to evaluate alternative control strategies (Samuel et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the importance of these factors is particularly critical for endemic Hawaiian species that continue to undergo steep population declines and range restrictions as climate warms. Like human malaria, spatial patterns of avian malaria are driven by exogenous temperatures, altitude, rainfall, and suitable habitat for larval mosquitoes to complete their life cycle (Balls et al 2004, Pascual et al 2008, Grillet et al 2010, Grillet et al 2014. As a result avian malaria in Hawaii may provide a seminal model to understand the environmental and ecological drivers of human malaria and to evaluate alternative control strategies (Samuel et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Knowledge of the influence of habitat factors on larval production is critical for understanding the spatial and temporal distribution patterns of mosquito vector species and for planning and implementing appropriate larval control strategies. 7,8 Despite five decades of intensive control efforts, Brazil continues to report the greatest proportion of malaria cases in the Americas. 9,10 Within Brazil, the incidence of malaria is almost exclusively (99.8% of the total number of cases) restricted to the Amazon Region, where a number of combined factors favor disease transmission and impair the use of standard control procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Moffett et al (2007) identified the growing population density as major factor in determining the malaria risk in Africa. Grillet et al (2010) ordinary least squares (OLS) regression models indicated that lower elevations, greater population density, and proximity to aquatic habitats cause disease persistence in northeastern Venezuela.…”
Section: Global Spatial Autocorrelation Analysismentioning
confidence: 99%